Deviant behavior : classical theories - Humphrey, John A., active 2021; Schmalleger, Frank (Los Angeles, CA : SAGE Publications, Inc., 2021)
What makes behavior deviant, and who gets to decide what deviance is? Deviant Behavior seeks to answer these questions and more. This compelling new text covers the social forces that shape deviance, the motivations and consequences of deviant behaviors, and how our definition of deviance changes over time. Authors John A. Humphrey and Frank Schmalleger discuss a wide range of deviant behaviors-from criminal acts to extreme forms of everyday behavior-and provide students the necessary foundation to understand the impact of globalization on traditional and emerging forms of deviance. Readers will explore deviance in the modern world using a systematic application of social and criminological theories to a range of deviant behaviors to help them better understand themselves, others, and society. Included with this title: The password-protected Instructor Resource Site (formally known as SAGE Edge) offers access to all text-specific resources, including a test bank and editable, chapter-specific PowerPoint® slides. Learn more.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Deviant behavior